一种降低南极磷虾油酸值的工艺研究 Technology of reducing acid value of Antarctic krill oil - 胥亚夫，俞存兵，余奕珂，郭忠，吴微，吕晶，郝兰 " XU Yafu, YU Cunbing, YU Yike, GUO Zhong, WU Wei, LYU Jing，HAO Lan" (Zhongguo youzhi)
旨在为南极磷虾油的品质提升提供技术参考，以南极磷虾油为原料，采用食品级硅酸镁对其进行脱酸处理，并以衡量南极磷虾油生产成本和产品品质的5个最重要指标（南极磷虾油得率、磷脂含量、酸值、流动性和透明度）为考察指标，通过单因素实验和正交实验确定最佳脱酸工艺条件。结果表明：南极磷虾油的最佳脱酸工艺条件为南极磷虾油与乙醇质量体积比1∶ 1，硅酸镁添加量15%（以南极磷虾油质量计）、反应时间1 h，在此条件下脱酸后，南极磷虾油得率为92.5%，酸值（KOH）由 11.53 mg/g降至5.74 mg/g，磷脂含量由53.36%降至52.33%，流动性和透明度均较好。综上，硅酸镁脱酸工艺可以在保留南极磷虾油营养成分磷脂的同时，实现其酸值的有效降低。 In order to provide technical reference for improving the quality of Antarctic krill oil, using Antarctic krill oil as the raw material and food-grade magnesium silicate as the deacidification agent, the oil was subjected to deacidification treatment. The most critical five indicators (yield of Antarctic krill oil, phospholipid content, acid value, fluidity and transparency）for assessing the production cost and product quality of Antarctic krill oil were used as indicators, and the optimal deacidification process conditions were determined through single factor experiments and orthogonal experiments. The results showed that the optimal deacidification process conditions were as follows: mass-volume ratio of Antarctic krill oil to ethanol 1∶ 1, magnesium silicate addition amount 15% (based on the mass of Antarctic krill oil), and reaction time 1 h. Under the optimal conditions, the yield of deacidfied Antarctic krill oil reached 92.5%, the acid value was reduced from 11.53 mgKOH/g to 5.74 mgKOH/g, the phospholipid content decreased from 53.36% to 52.33%, and both fluidity and transparency were improved. In conclusion, the magnesium silicate deacidification process can effectively reduce the acid value while retain its nutritional component phospholipid in Antarctic krill oil.